Model for Developing Student Entrepreneurial Intentions to Anticipate Educated Unemployment - Husnah Husnah; Harnida W. Adda; Munawarah Munawarah (LifeSciFi, 2023)
This research addresses the pressing issue of increasing unemployment among college graduates in Palu City, arising from the lack of opportunities in the formal job market. To combat this problem, the study proposes fostering creativity, initiative, innovation, and independence among graduates through entrepreneurial activities. The research aims to design and develop a model that stimulates students' entrepreneurial intentions to preempt the rise in educated unemployment in Palu City. The specific objectives are as follows: 1) Identify the level of entrepreneurial interest among students; 2) Test and analyze the implementation of the Student Entrepreneurial Intention Model, considering entrepreneurship education, achievement needs, and self-efficacy among students at Tadulako University, Palu; 3) Develop a Student Entrepreneurial Intention Model based on the Theory of Planned Behavior, tailored to the unique characteristics of Tadulako University students. Employing a survey method with a quantitative and qualitative descriptive approach, the research utilizes primary and secondary data, including questionnaires, interviews, and observations. The unit of analysis comprises students who took the Entrepreneurship Course during the Even Semester of 2014-2015 at Tadulako University. Data analysis employs descriptive and inferential techniques, specifically Partial Least Square (PLS). This research is expected to contribute to addressing the growing issue of educated unemployment by empowering students to embrace entrepreneurship as a viable career option and pave the way for a more sustainable and enterprising economy in Palu City.